Students’ Thinking Process in Solving HOTS Problem in Derivative Application Materials - Pratama, Aditya; Sudirman, Sudirman; As'ari, Abdur Rahman (Universitas Wiralodra, 2024)
In every mathematics learning process, it is crucial to identify students' thinking processes to observe and assess their mathematical thinking abilities. One way to comprehend students' thinking processes is by examining their work or their responses to problem-solving test questions. This research utilized Polya's framework, which comprises the four stages of problem-solving. One of the efforts to measure and improve students' problem-solving skills is by giving them High Order Thinking Skills (HOTS) questions. In this study, the researcher employed a qualitative approach, specifically the case study research type, to explore the thinking processes of students who make mistakes in solving higher-order thinking skills (HOTS) problems. Subjects in this study were collected by submitting HOTS-type questions to eleven 12th-grade students. The researcher chose one student with incorrect answers and with more complete writing than others to be the subjects. The results revealed that the subject engaged in the stages of understanding the problem, planning the solution, and executing the plan, but did not undertake the